The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1111/j.1439-0264.2012.01159.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Morphology of the Papillae Linguales and their Connective Tissue Cores in the Tongue of the Greater Japanese Shrew‐mole, Urotrichus talpoides

Abstract: The external morphology of the papillae linguales (papillae filiformes, papillae fungiformes and papillae vallatae) and their connective tissue cores (CTCs) of the greater Japanese shrew-mole (Urotrichus talpoides) were analysed by optical and scanning electron microscopy. Papillae filiformes were distributed over the dorsal surface of the apex linguae, and on the rostral and caudal regions of the corpus linguae but were less numerous in the mid-region. They were absent from the radix linguae. A pair of oval p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
(21 reference statements)
1
6
2
Order By: Relevance
“…The filiform papillae structure in other mammals such as giant panda was multifilamentous with meaningful secondary papillae (Pastor et al., ), different than alpaca. In contrast to our research, the appearance of filiform papillae in Japanese shrew mole varied depending of the area (Yoshimura et al., ). The shapes of filiform papillae were various between lingual areas, where in rostral part, the filiform papillae had one main sharp projection, in the middle region had two sharp projections, while in caudal section had three sharp projections (Yoshimura et al., ), which is different than in alpaca.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The filiform papillae structure in other mammals such as giant panda was multifilamentous with meaningful secondary papillae (Pastor et al., ), different than alpaca. In contrast to our research, the appearance of filiform papillae in Japanese shrew mole varied depending of the area (Yoshimura et al., ). The shapes of filiform papillae were various between lingual areas, where in rostral part, the filiform papillae had one main sharp projection, in the middle region had two sharp projections, while in caudal section had three sharp projections (Yoshimura et al., ), which is different than in alpaca.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our research, the appearance of filiform papillae in Japanese shrew mole varied depending of the area (Yoshimura et al., ). The shapes of filiform papillae were various between lingual areas, where in rostral part, the filiform papillae had one main sharp projection, in the middle region had two sharp projections, while in caudal section had three sharp projections (Yoshimura et al., ), which is different than in alpaca. Histologically, the structure of filiform papillae in alpaca resembles these papillae in other animals, especially Bactrian camel (Eerdunchaolu et al., ).…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, primary and secondary types of these papillae were mentioned in the same study (Can, Atalgın, Ates, & Takçı, 2016). In the some previous studies on mice (Toprak, 2006) and blind mice (Yoshimura, Shindo, & Kageyama, 2013), it is indicated that papillae filiformes are located in three different places of the tongue and their shapes are observed in three different types. The papillae in intermolar region of mice formed homocentric circles (Toprak, 2006).…”
Section: Discussionmentioning
confidence: 91%
“…In the previous studies, it is reported that dorsal faces of all papillae vallatae are flat (Ates, Akaydin Bozkurt, Kozlu, Alan, & Düzler, 2013;Can et al, 2016;Erdogan et al, 2016;Erdogan & Perez, 2014;Jackowiak & Godynicki, 2004;Yoshimura et al, 2013;Zheng & Kobayashi, 2006). However, circular extensions were determined on the tongues of wolves that were varying between 10 and 14 in number.…”
Section: Discussionmentioning
confidence: 97%
“…Studies that assessed the structure of the tongue in chosen mammals living in different habitats and receiving different diets have found there are species-specific morphological differences (Iwasaki and Miyata 1990 ; Chamorro et al 1993a , b ; Saber et al 2001 ; Jackowiak 2006 ; Toprak and Yilmaz 2007 ; Elsnasharty et al 2013 ; Yoshimura et al 2008 , 2013 ; Erdoğan et al 2015 , 2016 ; Goździewska-Harłajczuk et al 2015 , 2016 ; Akbari et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%